1982
DOI: 10.1007/bf00754338
|View full text |Cite
|
Sign up to set email alerts
|

The effect of client choice of therapist on therapy outcome

Abstract: This study compared the therapeutic progress of three randomly assigned groups (n = 14 in each group) of community mental health center clients: (a) clients who viewed a slide/sound presentation about all available therapists and chose their own therapist; (b) clients who viewed the presentation and were assigned to a therapist by the center's clinical director; (c) clients who were assigned to a therapist by the clinical director without seeing the presentation. There were no significant differences among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 80 publications
(125 reference statements)
1
25
0
Order By: Relevance
“…This incongruence between expressed and actual preferences is likely to account for many of the inconsistencies present in the literature. The findings of Manthei's (1982) study, carried out in a clinical setting, suggested that there may be a distinction between preference and choice. This study, carried out in analogue form, confirms and indeed emphasizes the need to differentiate between the two.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This incongruence between expressed and actual preferences is likely to account for many of the inconsistencies present in the literature. The findings of Manthei's (1982) study, carried out in a clinical setting, suggested that there may be a distinction between preference and choice. This study, carried out in analogue form, confirms and indeed emphasizes the need to differentiate between the two.…”
Section: Discussionmentioning
confidence: 99%
“…Items were suggested by other research (Manthei, 1982;Netzky, Davidson & Crunkleton, 1982) and the counselling literature in general. Items could be categorised as one of three types: (a) quality of the relationship items (e.g., Looks like the kind of person who will listen to me; Treats me with respect; Accepts me as I am); (b) physical and cultural similarity items (e.g., Is the same race as I am; Is attractive; Is the same sex as I am); (c) directive and non-directive aspects of counselling style items (e.g., Is able to help me figure out what to do; Will push me into doing what I ought to do; Tells me what to do).…”
Section: Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Glassman and Glassman (1981) found that women used personal experience and peer recommendations to select a physician, and patient satisfaction was determined primarily by physiciancontrolled factors such as providing sufficient relevant information about what to expect during pregnancy and offering continuity of care. Manthei et al (1982) manipulated patients' choice of health care providers in a community mental health center and then measured patient satisfaction. Surprisingly, the subjects did A 2 Â 2 full factorial between subjects experimental design was used to examine how three elements of the health care experience (patients' freedom to choose a physician; patients receiving their preferred physician; health care outcome) impacted on patient satisfaction with health care service.…”
Section: Patient Choicementioning
confidence: 99%
“…Furthermore, the preference type being honored (i.e., treatment, role, or psychotherapist characteristic) did not moderate either finding, suggesting that all types, when aggregated statistically, appear to have a consistent association with treatment dropout and outcome. However, only three studies in this meta-analysis specifically focused on the effect of preference match for psychotherapist characteristics (Manthei, Vitalo, & Ivey, 1982;Proctor & Rosen, 1981;ZIotnick, Elkin, & Shea, 1998), and none demonstrated an effect individually. Thus, although it may be that an effect is present, as suggested in the meta-analysis with the larger aggregated sample, additional research is needed to establish more definitely whether accommodating clients' preference for psychotherapist characteristics is associated with better treatment process and outcome.…”
mentioning
confidence: 97%